The Effect of Academic Pressure, Social Support, and Mental Health Students from Sharia Perspective - Alika Rahmadia; Marlya Fatira AK; Rizal Agus; Ahmad Kholil; M. Rikwan Effendi Salam Manik (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the influence of academic pressure, social support, and mental health from a sharia perspective on the achievement of Muslim students receiving the KIP-Kuliah (Kiliyah Student Assistance) at the Medan State Polytechnic. This research fills a gap in research that is still dominated by partial studies and has not integrated these three variables simultaneously within a framework of sharia values, particularly in the context of KIP-Kuliah students receiving vocational education. This study used a quantitative approach with a cross-sectional design. The sample consisted of 179 respondents selected using a purposive sampling technique. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was performed using multiple linear regression with SPSS version 26. The results showed that academic pressure had a negative and significant effect on student achievement with a value of -0.180, social support had a positive and significant effect with a value of 0.303, and mental health from a sharia perspective also had a positive and significant effect with a value of 0.380. Together, these three variables explained 19.7% of the variation in student achievement, while 80.3% was influenced by factors outside the research model. These findings underscore the importance of a holistic approach that integrates academic, social, and spiritual aspects in improving the achievement of KIP- Kuliah recipient students.